Modern migration process: new аpproaches in аnalysis (The Journal of Psychology and Sociology, 2022)
The article discusses research approaches to the analysis of migration, which is becoming one of the most important problems at the regional, national and international levels in the modern world. They also analyze migration processes in modern Kazakhstan. Migration can be viewed as a way of mass reaction of the population to the political, spiritual, socio-economic, and environmental changes taking place in the country. The process of migration affects the countries receiving and sending migrants differently depending on the level of development, migration processes affect the structure of the country and lead to the differentiation of its regions. While the governments of developing countries that send migrants today view their migrant citizens as potential investors and participants in the development process, in developed countries, on the contrary, the negative socio-political consequences of migration have now become apparent. In the article, with the help of a scientific analysis of the works of domestic and foreign authors, a priority approach is determined in the analysis of migration. And also through the analysis of statistical data, the features of migration processes in the territory of Kazakhstan are revealed.The analysis shows that since the beginning of the 21st century, the number of studies of “migration pessimists”, who give a negative assessment of migration and advocate limited migration, has increased. They associate negative consequences with migration, such as a decrease in income among the indigenous population, an increase in unemployment, an increase in social spending, a slowdown in economic growth, an increase in social tension caused by increased cultural differences, a worsening sanitary and epidemiological situation, the threat of terrorism, etc. For these reasons, today migration creates more negative forecasts. The difference between these views lies in the fact that most works written in an optimistic manner are more concerned with the theoretical aspects of the problem and are based on the economic consequences of migration for donor and recipient countries, while “pessimistic” works are based on empirical data and are aimed at more accurate analysis of the socio-economic, political, cultural, demographic, environmental consequences of migration.Key words: migration, internal migration, external migration, limited migration, migrant